Calcium Orthophosphate (CaPO4) Scaffolds for Bone Tissue Engineering Applications - V. Dorozhkin, Sergey (Journal of Biotechnology and Biomedical Science, 2018)
The chemical and structural similarities of calcium orthophosphates (abbreviated as CaPO4)to the mineral composition of natural bones and teeth have made them a good candidate for bone tissue engineering applications. Nowadays, a variety of natural or synthetic CaPO4-based biomaterials is produced and has been extensively used for dental and orthopedic applications. Despite their inherent brittleness, CaPO4 materials possess several appealing characteristics as scaffold materials. Namely, their biocompatibility and variable stoichiometry, thus surface charge density, functionality and dissolution properties, make them suitable for both drug and growth factor delivery. Therefore, CaPO4, especially hydroxyapatite (HA) and tricalcium phosphates (TCPs), have attracted a significant interest in simultaneous use as bone grafts and drug delivery vehicles. Namely, CaPO4-based three-dimensional (3D) scaffolds and/or carriers have been designed to induce bone formation and vascularization. These scaffolds are usually porous and harbor various types of drugs, biologically active molecules and/or cells. Over the past few decades, their application as bone grafts in combination with stem cells has gained much importance. This review discusses the source, manufacturing methods and advantages of using CaPO4 scaffolds for bone tissue engineering applications. Perspective future applications comprise drug delivery and tissue engineering purposes.
Keywords: Calcium orthophosphates; Hydroxyapatite; Tricalcium phosphate; Scaffolds; Bioceramics; Grafts; Biomedical applications; Tissue engineering.